PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA POP-UP BOOK TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS IV SD GUGUS X KOTA BENGKULU - Yuliani, Fera; Lusa, Herman; Tarmizi, Pebrian (PGSD FKIP Universitas Bengkulu, 2020)
This research aim to study the influence of the Discovery Learning model aided by Pop-Up Book media on student learning outcomes in Thematic learning. This research is quantitative research. The research method used a Quasi Experimental method with the design type Matching Only Pretest-Posttest Control Group Design. The population of this study is the IV grade Elementary school students of cluster X Bengkulu City. The samples were class IVB SDN 58 Bengkulu City and class IVB SDN 38 Bengkulu City. The sampling technique used the purposive sampling. The total sample are 42 students consisting of class IV B SDN 58 Bengkulu City with 21 students as the experimental class and class IV B SDN 38 Bengkulu City with 21 students as the control class. The research instrument used the knowledge learning test in the form of multiple choice questions given through Pretest and Posttest, for the results of learning attitude and skill aspects were used the observation sheets as the instrument. Data analysis technique in this research is quantitative analysis using descriptive statistics and inferential statistics. Based on the results of data processing, that estimated the results of the t-test show the value of t-count in Indonesian subjects are 2.96 and IPA are 5.03 greater than the value of t-table at a significant level of 5% are 2.02. Thus the hypothesis are proven and accepted. This shows that there is an influence of Discovery Learning Model aided by Pop-up book media on student learning outcomes in Thematic learning.Keywords: Discovery Learning, Pop-Up Book Media, Thematic, Learning Outcomes